Ethics of Medical Assistance in Dying for Non-Terminal Illness: A Comparison of Mental and Physical Illness in Canada and Europe - Birkness, Katharine; Rudnick, Abraham (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Medical assistance in dying (MAiD) is scheduled to be legalized in Canada as of March 2024 for individuals with mental disorder/illness as their sole underlying medical condition (MAiD MD-SUMC). As guidelines are being developed for the safe and consistent provision of MAiD MD-SUMC, sufficient consideration must be given to the interpretation of ambiguous terminology in current legislation, and to ensuring sound use of acceptable ethics principles in these interpretations.